A high-quality chromosome-level genome of wild Rosa rugosa. (9th September 2021) - Zang, Fengqi; Ma, Yan; Tu, Xiaolong; Huang, Ping; Wu, Qichao; Li, Zhimin; Liu, Tao; Lin, Furong; Pei, Surui; Zang, Dekui; Zhang, Xuemei; Zheng, Yongqi; et al.
Abstract: Rosa rugosa is an important shrub with economic, ecological, and pharmaceutical value. A high-quality chromosome-scale genome for R. rugosa sequences was assembled using PacBio and Hi-C technologies. The final assembly genome sequences size was about 407.1 Mb, the contig N50 size was 2.85 Mb, and the scaffold N50 size was 56.6 Mb. More than 98% of the assembled genome sequences were anchored to seven pseudochromosomes (402.9 Mb). The genome contained 37, 512 protein-coding genes, with 37, 016 genes (98.68%) that were functionally annotated, and 206.67 Mb (50.76%) of the assembled sequences are repetitive sequences. Phylogenetic analyses indicated that R. rugosa diverged from Rosa chinensis ∼ 6.6 million years ago, and no lineage-specific whole-genome duplication event occurred after divergence from R. chinensis . Chromosome synteny analysis demonstrated highly conserved synteny between R. rugosa and R. chinensis, between R. rugosa and Prunus persica as well. Comparative genome and transcriptome analysis revealed genes related to colour, scent, and environment adaptation. The chromosome-level reference genome provides important genomic resources for molecular-assisted breeding and horticultural comparative genomics research.